Positive Pressure for Obesity Hypoventilation Syndrome - Arijit Chanda; Jeff S. Kwon; Armand John Wolff; Constantine A. Manthous (Pulmonary Medicine)
Obesity is increasing world-wide; obesity hypoventilation syndrome (OHS), formerly Pickwickian syndrome, has increased in parallel. Despite its prevalence, OHS has not been studied well, but there is abundant evidence that it is tightly linked with sleep-disordered breathing, most commonly obstructive sleep apnea. This article reviews the pathophysiology of OHS as well as the literature regarding the benefits of treating this disorder with positive airway pressure. We also emphasize that while positive pressure treatments may temporize cardiopulmonary disease progression, simultaneous pursuit of weight reduction is central to long-term management of this condition.